Correlation of hypoxia inducible factor-1α and vascular endothelium growth factor in rat myocardium during aerobic and anaerobic exercise (Medical Journal of Indonesia, 2012)
Background: Exercise increases the need for oxygen to generate ATP through oxidative phosphorylation. If the high energy demand during exercise is not balanced by sufficient oxygen supply, hypoxia occurs in skeletal muscle tissue leading to upregulation of hypoxia inducible factor-1α (HIF-1α). The activity of HIF-1α increases the expression of various genes in order to reduce the metabolic dependence on oxygen and to increase oxygen supply to the tissue, e.g., VEGF which plays a role in angiogenesis. In myocardium, it is unclear whether exercise leads to hypoxia and whether HIF-1α and VEGF play a role in the mechanism of hypoxic adaptation. This study aimed to investigate the correlation of HIF-1α and VEGF in heart muscle tissue of rats during aerobic and anaerobic exercise.Methods: A rat treadmill was used with a specific exercise program for 1, 3, 7 and 10 days. The concentrations of HIF-1α and VEGF were measured the myocardium.Results: Both, HIF-1α protein and VEGF were increased (p < 0.05) in the groups with aerobic and anaerobic exercise. Concentrations of HIF-1α were highest on the first day of activity, being higher in the anaerobic than in the aerobic group (156.8 ± 33.1 vs. 116.03 ± 5.66). Likewise, the highest concentration of VEGF in the group with anaerobic exercise occurred on the first day (36.37 ± 2:35), while in the aerobic group, VEGF concentration was highest on day 3 (40.66 ± 1.73). The correlation between the myocardial tissue consentrations of HIF-1α and VEGF is moderate (r = 0.59) in the aerobic group and strong in the anaerobic group (r = 0.69).Conclusion: Aerobic and anaerobic exercise increase HIF-1α and VEGF concentrations in rat myocardium in specific patterns. The anaerobic condition triggers vascularization stronger and obviously earlier than aerobic exercise. (Med J Indones. 2012;21:133-40)Keywords: Exercise, HIF-1α, myocardium, VEGF